Evaluating an Optimal Corporate Income Tax System for Harmonization in the African Union - Chiromo, Samuel John; Schutte, Danie (Yayasan Ilomata, 2024)
Harmonizing corporate income tax (CIT) is spotlighted in economic integration debates. These debates have reached no consensus regarding the best CIT system to be adopted in various economic integrations, including the African Union (AU). This study aimed to determine the best tax system for CIT harmonisation in the AU. The study adopted a qualitative research method by collecting data through interviews. The study used purposive sampling to identify 30 participants drawn from the African Tax Administration Forum (ATAF) and large international accounting firms, namely KPMG, PWC and Deloitte. The study revealed that a new system called the Africa hybrid tax system or the Africa blended tax system should be implemented for effective and efficient CIT harmonisation in the AU. This system should address the shortcomings of both the classical and the imputation tax systems. The study recommended that technology and adequate resources are crucial for successfully implementing the African hybrid tax system. Therefore, member states should jointly invest in technology and resources to facilitate the implementation of the African hybrid tax system for CIT harmonisation in the AU.